Aerobnye vozmoznosti i sostojanie zdorov'ja: Kliniko-morfofunkcional'nye paralleli - Dudina, E. A. (Teorija i Praktika fiziceskoj Kul'tury, 2006)
The purpoce of the research was the clinic-morphofunctional parallels between the state of health and the level of aerobic power potential of the elite athletes endurance training.